O Superior Tribunal Militar durante a ditadura militar brasileira (1974-1985) - Coitinho, Angélica do Carmo (2018)
This research aims to understand how the Superior Military Courty (STM) proceeded to try those accused of crimes against national security in the political conjuncture of the process known as the liberalization of military dictatorship during the governments of generals Ernesto Geisel and João Baptista Figueiredo (1974-1985). From this, it is sought to identify how the STM dealt with the progressive reduction of authoritarian laws and the changes in the National Security Law (LSN), in order to understand if there was a process of liberalization and if we can affirm that it took effect in the performance of military justice. The liberalization period was chosen for this study on the decision-making behavior of the STM, since the measures taken by the government - such as the permitting of elections, the new LSN, the repeal of institutional acts, the enactment of the amnesty law, the return of partisan plurality and some freedom for the workings of the workers' movements - did not mean the existence of less severe sentences. On the other side, the trial of defendants for bank robbery, for example, resulted in very high penalties between 1974 and 1979, and also the possibility that trade unionists might be punished by the court during the period known as the new trade union movement in in the late 1970s and early 1980s. In addition, I intend to contribute to studies that seek to understand the role assumed by the STM during this period, since the institution still seeks to justify the period in which it acted in the trial of defendants of crimes politicians ascribing to themselves the role of a justice linked to a state governed by the rule of law and therefore a guarantee of citizens' rights, even at that time, when they lived under an authoritarian regime.